Study of Association of C-Reactive Protein with Coronary Collateral Development (Cardiovascular Journal, 2010)
Background: In vitro studies have shown that C-reactive protein (CRP) attenuates nitric oxide production and inhibits angiogenesis, which may result in impaired collateral development. The aim of this study was to investigate the association between CRP levels and the extent of coronary collaterals. Materials and methods: A total of 100 patients who had a stenosis of >95% in any major coronary artery in angiograms were included in the study. The CRP was measured from a venous blood sample with a high-sensitivity assay. Collaterals of the epicardial coronary arteries were then studied and graded in a scale of 0 - 3 according to Rentrop classification. Results: Mean age was 49.6 years and 86% were male. The mean CRP level was found 15.57 ±12.85 mg/L in grade 0 (n =25 ), 11.38± 11.11 mg/L in grade I( n=20 ), 9.22± 10.15 mg/L in grade II ( n=34 ) and 8.97±8.44 mg/L in grade III (n =21) collateral group. The mean CRP values reduced significantly (p